Non-Punitive Policy in Addressing Violence and Sexual Harassment Among Middle School Students in Sleman Regency - Nabila Ihza Nur Muttaqi; Chandra Dewi Puspitasari; Iffah Nur Hayati; Puji Wulandari Kuncorowati; Setiati Widhiastuti (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2026)
This study aims to analyze non-penal policies implemented in addressing violence and sexual abuse among junior high school students in Sleman Regency. Violence and sexual abuse in educational settings, particularly at the junior high school level, are pressing issues that affect students' physical and psychological well-being. Non-penal policies, which focus on prevention, victim recovery, and education for students and educators, are expected to be a more humane alternative to legal approaches that tend to be reactive. This study uses a qualitative approach with a literature study method, which examines relevant policies, as well as reports and official documents available in Sleman Regency. The findings show that effective non-penal policies involve various elements, such as counseling for students and educators, establishing a safe reporting mechanism for victims, and implementing educational programs on sexual violence. In addition, the success of these policies also depends on the commitment of schools and the support of parents and the community. This study recommends that non-penal policies be expanded and implemented more comprehensively in all schools in Sleman Regency to create a safe educational environment that supports the recovery of victims of sexual violence and abuse.